Pengaruh Motivasi Kerja terhadap Kinerja Aparatur Sipil Negara melalui Komitmen Organisasional sebagai Variabel Intervening pada Biro Administrasi Pembangunan Kantor Gubernur Kalimantan Barat - S, Yuana; Rizal, Maulana Filani; W, Irvan Wibowo; Febrianawati, Febrianawati; Immanuel, Deandra (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to examine the effect of work motivation on the performance of Civil Servants (ASN) with organizational commitment serving as an intervening variable at the Development Administration Bureau of the West Kalimantan Governor’s Office. The fluctuating performance of employees amidst high administrative and coordination workloads constitutes the primary rationale for conducting this research. An explanatory quantitative approach was employed, utilizing a saturated sampling (census) technique involving the entire population of 33 employees. Primary data were collected through the distribution of structured questionnaires using a Likert scale. Data analysis was conducted using variance-based Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach through SmartPLS software. The results of the path analysis indicate that work motivation has a positive and significant effect on organizational commitment. However, work motivation does not have a significant direct effect on the performance of civil servants. Furthermore, the mediation analysis confirms that organizational commitment is unable to perform its role as an intervening (mediating) variable in the relationship between work motivation and employee performance. The findings suggest that variations in ASN performance within the institution are not primarily driven by individual psychological factors, such as intrinsic motivation or emotional attachment to the organization. Instead, employee performance appears to be more strongly influenced by external structural factors beyond the scope of the research model.